Harmonization of Security Legislation within the Framework of Union State - D. V. Perevalov (Евразийская интеграция: экономика, право, политика, 2025)
Aim and tasks. To develop an approach, the use of which will allow for the systematic harmonization and unification of the legislation of the Republic of Belarus and the Russian Federation within the Union State in the field of security, taking into account the specifics of national legal systems. To analyze the experience of harmonization and unification of legislation in the USSR and the European Union. To conduct a comparative legal analysis of legislative acts of Belarus and Russia regulating relations in the field of security. To formulate proposals for the formation of a homogeneous legal system of the Union State in the field of security.   Methods. In the course of the study, comparative legal, deductive and systemic methods were used, as well as methods of analysis, comparison and generalization.   Results. The study showed that for the harmonization and unification of the legislation of Belarus and Russia within the Union State in the field of security, the most appropriate is to use the experience of the USSR in adopting and implementing the Fundamentals of Legislation in various industries.   Conclusions. In the modern period, the use of the proposed approach will ensure consistent and systemic legal regulation in the sp here of ensuring security by adopting the Fundamentals of Legislation of the Union State on Ensuring National Security and, subsequently, the Fundamentals of Legislation of the Union State in Individual Spheres and in Individual Areas. Based on these Fundamentals, relevant national laws can be adopted.